A Study on Roles of Physical Therapy in Community-Based Rehabilitation: Exploring the Roles and Training Needs of Physical Therapists in Community-Based Rehabilitation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Through a community-based rehabilitation (CBR) procedure, physical therapists could improve personal satisfaction for people with disabilities. Members are encouraged to explore their views on the issues facing people with disabilities in the existing recovery administrations. Methodologies for dealing with all issues were distinguished cooperatively and arranged by necessity according to the meaning of the issue. Meetings and perception were used to evaluate CBR yields. The results found that physical therapists had different jobs in CBR, depending on the conditions of the family. For apply for CBR, they need a high level of adaptability and a wide range of skills. The arrangement of such physical therapists requires an improvement in a training program that is more customer-focused in the community.